2022
DOI: 10.3389/fnut.2022.899421
|View full text |Cite
|
Sign up to set email alerts
|

The Methanol Extract of Polygonatum odoratum Ameliorates Colitis by Improving Intestinal Short-Chain Fatty Acids and Gas Production to Regulate Microbiota Dysbiosis in Mice

Abstract: The potential impacts of methanol extract from Polygonatum odoratum on (YZM) colonic histopathology, gut gas production, short-chain fatty acids (SCFAs), and intestinal microbiota composition were evaluated with dextran sulfate sodium (DSS)-induced colitis mice in this study. These results indicated that YZM increased colon length and ameliorated colonic histopathology in DSS-induced colitis mice. Moreover, YZM administration reversed intestinal microbiota compositions leading to the inhibition of H2S-related … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 41 publications
0
12
0
Order By: Relevance
“…Species richness is more responsive to the Shannon index, but species evenness is more sensitive to the Simpson index.The chao1 index reflects the community species richness; the higher the value, the higher the species richness. Good's Coverage reflects the OTU coverage of the sample (31).…”
Section: Alpha and Beta Diversity Analysismentioning
confidence: 99%
“…Species richness is more responsive to the Shannon index, but species evenness is more sensitive to the Simpson index.The chao1 index reflects the community species richness; the higher the value, the higher the species richness. Good's Coverage reflects the OTU coverage of the sample (31).…”
Section: Alpha and Beta Diversity Analysismentioning
confidence: 99%
“…In the last decade, gut microbiota has become a hot research topic and shown as a crucial regulator for substrate metabolism, energy balance, and health status in organisms (35)(36)(37)(38). A growing number of reports documented that many chronic diseases (e.g., obesity and T2MD) were associated with gut microbiota dysbiosis (39)(40)(41), and TCM played an important and positive role in improving obesity-related metabolic diseases (20)(21)(22)42).…”
Section: Discussionmentioning
confidence: 99%
“…After fermentation, the vial was restored to room temperature after which the gas was automatically analyzed using a gas analyzer to determine gas composition and concentration ( 14 ).…”
Section: Methodsmentioning
confidence: 99%